Foot drop following primary total hip arthroplasty. Issue 2 (March 2020) - O'Brien, Seamus; Gallagher, Nicola; Spence, David; Bennett, Damien; Dennison, Janice; Beverland, David E
Introduction: Foot drop is a potentially debilitating complication following injury to the sciatic nerve during primary total hip arthroplasty (THA). The aim of this study was to determine the incidence, risk factors and outcome of this complication within one large surgical practice. Methods: We analysed the records of 10, 624 primary THAs carried out between January 1993 and November 2017 using a posterior approach. All were under the care of the senior author. Results: Overall, there were 47 cases (0.44%) of foot drop, but over time the incidence dropped from 0.6% to 0.3% ( p = 0.033). Preoperative protrusio acetabulae ( p < 0.001), female sex ( p < 0.001) and junior grade of surgeon ( p < 0.009) were all significant risk factors. In this series, dysplasia was not a risk factor. 1 year postoperatively, 25 (53.2%) had complete recovery, 12 (25.5%) had ongoing sensory deficit but normal power, and 10 (21.3%) had a residual sensory-motor deficit. Conclusion: Take home message:- In this series, protrusio acetabulae, female sex and junior grade of surgeon were significant risk factors for foot drop following primary THA.